Do impresso ao digital : o processo de transição no jornalismo local e do “interior” - Santos, Ednilson Barbosa (2019)
The main objective of this research was to investigate the specificities of the transition process from print to digital in ‘local journalism’ and ‘interior’. It was based on the premise that the literature on journalism practiced in the Internet environment (under different denominations) has concentrated its empirical studies on the so-called big press, disregarding variables present in other contexts. Recognizing this gap, this Master’s research sought to reflect on the business models, technological options and influence of the geographical context observable in two recent experiences of this transition in the Northeast Region: that of the weekly newspaper Cinform, from Aracaju, capital of Sergipe, and the newspaper O Mossoroense, from Mossoró, in the interior of Rio Grande do Norte. In this direction, it sought to identify the singularities of these two processes, based on the characteristics and “phases” of digital journalism observed in studies on newspapers of “national prestige”. For theoretical reasons, he used contributions from Geographies of Communication, Regional Communication, and Digital Journalism and Hypermedia. As a methodological course, a combination of procedures of systematic observation, documentary analysis and content analysis were used, since this is an exploratory research (without parameters of similar studies previously consolidated) for descriptive, diagnostic and prospective purposes. It was then possible to demonstrate that the centenary of the potiguar daily kept up to date with the technologies of journalistic production until joining the digital world, while the young Sergipe weekly adopted as a “innovation” a model of transpositive journalism, typical of the first era of Internet, whose novelty is to distribute the weekly edition in pdf, via the application of mobile messages.